Moving with Ease: Feldenkrais Method Classes for People with Osteoarthritis. (3rd September 2013) - Webb, Robert; Cofré Lizama, Luis Eduardo; Galea, Mary P.
Abstract : Objective . To investigate the effects of Feldenkrais Method classes on gait, balance, function, and pain in people with osteoarthritis. Design . Prospective study with pre-/postmeasures. Setting . Community. Participants . Convenience sample of 15 community-dwelling adults with osteoarthritis (mean age 67 years) attending Feldenkrais Method classes. Intervention . Series of Feldenkrais Method classes, two classes/week for 30 weeks. Main outcome measures: Western Ontario and McMaster Universities osteoarthritis scale, Human Activity Profile, stair climbing test, 6-minute walk test, timed up-and-go test, Four Square Step Test (4SST), gait analysis, and assessment of quality of life (AQoL). Results . Participants improved on the 4SST and on some gait parameters. They also reported a greater ease of movement. Conclusions . A 30-week series of Feldenkrais classes held twice per week was feasible in the community setting. The lessons led to improvements in performance of the four square step test and changes in gait.